PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Bina Marga Semarang) - Tri Wahyuningsih, 08.05.51.0054; Sutomo, Y. (Students Journal of Economic and Management, 2012)
This research is a study that examined the influence environme work, motivation and job satisfaction on the performance of employees at the Department of Highways Semarang.Sesuai title above performance is affected by several factors that support good work environment factors, motivation and job satisfaction, or it could be other factors beyond of the third factor. In this study, researchers used purposive sampling and sample scored 60 sanmpel employees. Employee data is then tested using KMO and Loading factors. The results showed that the value of KMO eligiblefor further analysis to Loading factor, then factor analysis loading declared invalid. Further analysis using multiple regression analysis to explain the relationship between these variables. The result is a work environment positive and significant effect on the performance of employees, while the motivation was not a significant and positive effect on employee performance and satisfaction, and a significant positive effect On employee performance. This study has a limitation that is based on research, the limitations of this study is the value of Adjusted R square of 0.608. This indicated that the work environment, motivation, and job satisfaction hany mampumenjelaskan 60.8% each variable of the variable employee performance. While 39.2% of employees in the performance of the Department of Highways Semarang influenced by actors - other factors outside the work environment, motivation and job satisfaction.